Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Hybrid framework combining machine learning with mechanism models for enhanced forecasting of biomass gasification products - Jiaming Song; Zongqi Chen; Haining Tang; Hong Ding; Shiliang Wu; Zhou Liu; Feng Gong (Bioresource Technology, 2026)

Targeting S100A4+ macrophages to reverse radiation-induced Leydig cell fibrosis with a therapeutic nanosystem - Yewei Bao; Heng Gong; Weihao Sun; Lei Wang; Tianqi Wang; Boyang Zhang; Guanyu Ren; Shuguang Piao; Cheng Zheng; Jiaming Guo; Linhui Wang; Xinxin Gan (Chemical Engineering Journal, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

Corrigendum to “Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms” [Catena 254 (2025) 108882] - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Efficient separation and recycling of waste wind turbine blades through in-situ generation of peroxyacetic acid - Xinyi Xu; Jiaming Liu; Jiachun Feng; Bin Chen; Shiwen Gong; Xueer Ouyang; Changxu Qin; Gang Luo; Shicheng Zhang (Resources, Conservation and Recycling, 2025)

A deep learning-based data augmentation method for marine mammal call signals - Jiaming Jiang; Wanlu Cheng; Shengwen Gong; Jingjing Wang (Frontiers in Marine Science, 2025)
In marine ecology research, it is crucial to accurately identify the marine mammal species active in the target area during the current season, which helps researchers understand the behavioral patterns of different species and their ecological environment. However, the difficulty and high cost of collecting marine mammal calls, coupled with limited publicly available datasets, result in insufficient data for support, making it difficult to obtain accurate and reliable identification results. To address this problem, we propose MarGEN, a deep learning-based augmentation method for marine mammal call signal data. This method processed the call data into Mel spectrograms, then designed a self-attention conditional generative adversarial network to generate new samples of Mel spectrograms that were highly similar to the real data, and finally reconstructed them into call signals using WaveGlow. The classification experiments on the calls of four Marine mammals show that MarGEN significantly enriches the diversity and volume of the data, increasing the classification accuracy of the model by an average of 4.7%. The method proposed in this paper greatly promotes marine ecological protection and sustainable development, while effectively advancing research progress in bionic covert underwater acoustic communication technology.

Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Tree age estimation across the U.S. using forest inventory and analysis database - Jiaming Lu; Chengquan Huang; Karen Schleeweis; Zhenhua Zou; Weishu Gong (Forest Ecology and Management, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Mechanistic insights into the hydrogel-supported catalyst for superior oxygen evolution performance - Yuxuan Wei; Lingling Xu; Kefan Shi; Hanwen Gong; Jiaming Hu; Xianghao Zhang; Meilan Pan; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

Hotspots of wetland loss to impervious surfaces in the conterminous United States - Zhenhua Zou; Chengquan Huang; Megan W. Lang; Ling Du; Greg McCarty; Jeffrey C. Ingebritsen; Jane Harner; Rusty Griffin; Weishu Gong; Jiaming Lu (Science of The Total Environment, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)

Chemical constituents from the leaves of psidium guajava linn. and their chemotaxonomic significance - Guangxin Zhou; Jiaming Zhao; Chang Gong; Jixuan Xu; Ce Song; Dali Meng (Natural Product Research, 2023)

Effects of arsenic–iron–dissolved organic matter interactions on arsenic mobilization: Insight from column experiments - Ziyi Xiao; Xianjun Xie; Kunfu Pi; Jiaming Gong; Yanxin Wang (Journal of Hydrology, 2023)